2021
DOI: 10.21203/rs.3.rs-583442/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression Status and Prognostic Values of SOCS Family Genes in Non-small Cell Lung Cancer

Abstract: Backgroud:Suppressors of cytokine signaling (SOCS) family play important roles in the development of cancers by inhibiting the transmission of the Janus kinases–signal transducers and activators of transcription (JAK-STAT) signaling pathway. However, the expression patterns and prognostic value of SOCS family genes in non-small cell lung cancer (NSCLC) remains unclear. Methods: The SOCS family genes expression profiles were explored using ONCOMINE and GEPIA online tools. The mutation and copy number alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Slc25a24, Cnpy2 and BAX overexpression was reported in breast cancer 66 . Similar to our work, a recent study reported on the overexpression of Plin3 in the breast cancer tissues in comparison with healthy breast 67 . HMGB1 is considered a ubiquitous protein, which has a role as a nuclear cofactor in the regulation of transcription 68 .…”
Section: Discussionsupporting
confidence: 92%
“…Slc25a24, Cnpy2 and BAX overexpression was reported in breast cancer 66 . Similar to our work, a recent study reported on the overexpression of Plin3 in the breast cancer tissues in comparison with healthy breast 67 . HMGB1 is considered a ubiquitous protein, which has a role as a nuclear cofactor in the regulation of transcription 68 .…”
Section: Discussionsupporting
confidence: 92%
“…This protein mediates a connection between LD and mitochondria and presumably displays a cytoprotective effect via decreasing fatty acid toxicity (reviewed in Kimmel and Sztalryd 2014). PLINs have been shown as suitable markers for LDs in human tumors (Zhang et al 2018(Zhang et al , 2020(Zhang et al , 2021. In breast cancer, high expression of PLIN1 predicted a longer overall patient survival, while overexpression of PLIN2 indicated poor overall patient survival (Zhang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…PLINs have been shown as suitable markers for LDs in human tumors (Zhang et al 2018(Zhang et al , 2020(Zhang et al , 2021. In breast cancer, high expression of PLIN1 predicted a longer overall patient survival, while overexpression of PLIN2 indicated poor overall patient survival (Zhang et al 2021). Determining the respective PLIN proteins aided the differentiation of tumor types in liposarcomas (Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…And as one of the redox-dependent factors of tumor, PLIN5 indirectly affected the redox state of adipose tissue in GC ( 34 ), which was potentially related to the prognosis of patients with GC. Additionally, the prognostic value of PLIN5 has been explored in many cancers, including breast cancer ( 35 ), pancreatic cancer ( 24 ), hepatocellular carcinoma ( 25 ), and so on; however, we first investigated the prognostic role of mutated PLIN5 in patients with GC. All the above evidence indicated that ELP6 and PLIN5 mutations were probably prognostic biomarkers for patients with GC.…”
Section: Discussionmentioning
confidence: 99%